White Collar Crime - Ike Pratiwi Br Limbong; Sarmila Dalimunthe; Sahlan Sahlan (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This white-collar crime phenomenon has one characteristic, namely the use of positions and the classic concept of white-collar crime is always focused on the government. Therefore, white-collar crime or white-collar crime is generally only discovered after causing many victims, because it is not easy to find out, because its nature is integrated into the system, so that victims and the public cannot see it with the naked eye.